2019
DOI: 10.3389/fncel.2019.00461
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial Current Stimulation Alters the Expression of Immune-Mediating Genes

Abstract: Despite its extensive use in clinical studies, the molecular mechanisms underlying the effects of transcranial direct current stimulation (tDCS) remain to be elucidated. We previously described subacute effects of tDCS on immune- and stem cells in the rat brain. To investigate the more immediate effects of tDCS regulating those cellular responses, we treated rats with a single session of either anodal or cathodal tDCS, and analyzed the gene expression by microarray; sham-stimulated rats served as control. Anod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 50 publications
(72 reference statements)
0
20
0
Order By: Relevance
“…Osteopontin is a pleiotropic protein highly expressed in the CNS during neuroinflammatory processes associated with infections (Brown et al., 2011; Jin et al., 2006), injury (Chan et al., 2014; Hashimoto et al., 2003; Li et al., 2017), ischemic stroke (Gliem et al., 2015; Rabenstein et al., 2019; Riew et al., 2019), and neoplasia (Szulzewsky et al., 2018). Osteopontin has even been suggested as a prognostic blood biomarker, for example, after hypoxic brain injury or trauma (Gao et al., 2020; Li et al., 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Osteopontin is a pleiotropic protein highly expressed in the CNS during neuroinflammatory processes associated with infections (Brown et al., 2011; Jin et al., 2006), injury (Chan et al., 2014; Hashimoto et al., 2003; Li et al., 2017), ischemic stroke (Gliem et al., 2015; Rabenstein et al., 2019; Riew et al., 2019), and neoplasia (Szulzewsky et al., 2018). Osteopontin has even been suggested as a prognostic blood biomarker, for example, after hypoxic brain injury or trauma (Gao et al., 2020; Li et al., 2017).…”
Section: Discussionmentioning
confidence: 99%
“…We previously demonstrated that osteopontin counteracts the LPS‐induced proinflammatory response of microglia in vitro and after ischemic stroke (Rabenstein et al., 2016), drives microglial polarization toward an antiinflammatory phenotype (Ladwig et al., 2017), and consequently reduces secondary neurodegeneration in the thalamus (Ladwig et al., 2019; Schroeter et al., 2006). Furthermore, osteopontin mediates the proliferation and migration of neural stem cells toward the lesion site after stroke (Rabenstein et al., 2019; Rogall et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…tDCS has been largely studied for its effects on synaptic plasticity and neuronal excitability [ 16 , 17 ], and different studies in animal models have shown its effects on brain gene expression. In rat cerebral cortices, the administration of tDCS was observed to modulate the expression of several genes involved in synaptic plasticity, such as neurotransmitter receptors [ 22 ], plasticity related genes [ 71 ], and genes coding for the major histocompatibility complex I [ 21 ]. In addition, a study on C57BL/6 mice revealed that tDCS acts on synaptic plasticity through the modulation of Bdnf expression [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, anodal stimulation is known to depolarize neurons, to increase the probability of action potentials occurring and to induce synaptic plasticity [ 16 , 17 , 18 ]. The effects of tDCS on brain gene expression have been previously assessed in different animal models, revealing its ability to modulate the expression of genes involved in the mechanisms of synaptic plasticity and neuronal activity [ 19 , 20 , 21 , 22 ]; however, to date no studies have investigated its effects at the blood level.…”
Section: Introductionmentioning
confidence: 99%
“…tES approaches are targeted to have direct effects on brain functions which can include modulating perfusion ( Zheng et al, 2011 ; Stagg et al, 2013 ; Shin et al, 2020 ), clearance mechanisms ( Cancel et al, 2018 ), and the immune response ( Rabenstein et al, 2019 ). tES, from a theoretical perspective, may be applicable for preventing acute neuroinflammation or to directly address the neurological manifestations of COVID-19 infection.…”
Section: Introductionmentioning
confidence: 99%